2017
DOI: 10.5114/aoms.2016.63193
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial comparing hemodynamic responses to ketamine-propofol combination (ketofol) versus etomidate during anesthesia induction in patients with left ventricular dysfunction undergoing coronary artery bypass graft surgery

Abstract: IntroductionAnesthesia induction is often accompanied by a period of hemodynamic instability, which could be a significant problem in patients with compromised ventricular function. The aim of this study is to compare the hemodynamic responses to etomidate versus a combination of ketamine and propofol (ketofol) for anesthetic induction in patients with left ventricular dysfunction undergoing coronary artery bypass graft (CABG) surgery.Material and methodsIn a double-blind randomized clinical study, a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…However, for infants and young children whose organ systems are not fully developed, conventional general anesthesia often has an inhibitory effect on respiratory function (18). For example, propofol is a widely used opioid analgesic in clinical practice with an excellent analgesic effect (19). However, propofol can decrease vagal tone, resulting in low extent of pulmonary expansion and collapse due to participation of vagus nerve in pulmonary stretch reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…However, for infants and young children whose organ systems are not fully developed, conventional general anesthesia often has an inhibitory effect on respiratory function (18). For example, propofol is a widely used opioid analgesic in clinical practice with an excellent analgesic effect (19). However, propofol can decrease vagal tone, resulting in low extent of pulmonary expansion and collapse due to participation of vagus nerve in pulmonary stretch reflexes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Propofol, a widely acknowledged intravenous anesthetic used for induction of anesthesia in open heart surgery, possesses dose-dependent cardiovascular depressant properties leading to hypotension. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Zeballos et al ( 17 ) demonstrated that ketamine alone was unable to adequately relax muscles and ease pain, and that a higher dose was required for anesthesia; however, this may result in increased oral secretion, glossocoma, prominent agitation during the recovery period and even respiratory depression in serious cases. Consequently, ketamine is clinically combined with propofol for anesthesia to reduce the side effects and the dose of ketamine required ( 18 ). Hayes et al ( 19 ) reported that children who were administered ketamine and propofol for anesthesia had a lower likelihood of being restless during the recovery period compared with those who received ketamine alone.…”
Section: Discussionmentioning
confidence: 99%
“…glossocoma, prominent agitation during the recovery period and even respiratory depression in serious cases. Consequently, ketamine is clinically combined with propofol for anesthesia to reduce the side effects and the dose of ketamine required (18).…”
Section: Characteristicsmentioning
confidence: 99%